2014
DOI: 10.1016/j.jbankfin.2014.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Trademarking status and economic efficiency among commercial banks: Some evidence for the UK

Abstract: a b s t r a c tAs competition in the banking sector has intensified over the last two decades, commercial banks have started to use trademarks to differentiate their products and services from those offered by their competitors. Less clear are the implications of the trademarking activities on the commercial banks' performance. In this paper, we compare the cost and profit efficiency of trademarking and non-trademarking banks in the UK, over the period 2001-2013 using stochastic frontier methods. We use Propen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A restriction of the alternative profit model is that the degree to which banks can exert an influence on the price of outputs will depend on the given input prices, the given quantities of outputs and the technological constraints (Koetter, 2006). The alternative profit model has been widely used in the banking literature (Maudos et al, 2002;Bos and Kool, 2006;Koetter, 2006;Pasiouras et al, 2009;Duygun et al, 2014) Since this paper focuses on the impact of country-level environmental variables such as the cross-country variations in creditor rights and information sharing on bank profit (in)efficiency, we opt for the Battese and Coelli (1995) SFA model in order to estimate bank profit (in)efficiency 8 . This estimation of the frontier accommodates panel data and allows to 6 Efficiency estimations have some distinct advantages over accounting-based measures of performance such as financial ratios (Berger and Humphrey, 1997;Bauer et al, 1998).…”
Section: Measuring Profit (In)efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…A restriction of the alternative profit model is that the degree to which banks can exert an influence on the price of outputs will depend on the given input prices, the given quantities of outputs and the technological constraints (Koetter, 2006). The alternative profit model has been widely used in the banking literature (Maudos et al, 2002;Bos and Kool, 2006;Koetter, 2006;Pasiouras et al, 2009;Duygun et al, 2014) Since this paper focuses on the impact of country-level environmental variables such as the cross-country variations in creditor rights and information sharing on bank profit (in)efficiency, we opt for the Battese and Coelli (1995) SFA model in order to estimate bank profit (in)efficiency 8 . This estimation of the frontier accommodates panel data and allows to 6 Efficiency estimations have some distinct advantages over accounting-based measures of performance such as financial ratios (Berger and Humphrey, 1997;Bauer et al, 1998).…”
Section: Measuring Profit (In)efficiencymentioning
confidence: 99%
“…This SFA model provides estimates of bank efficiency and its covariates in a single-stage and has been used in numerous studies that examine the determinants of bank efficiency (e.g. Fiordelisi and Mare, 2013;Duygun et al, 2014). Furthermore, we use the alternative profit efficiency model (Humphrey and Pulley, 1997), which allows for some degree of market power and is commonly used in bank efficiency studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A restriction of the alternative profit model is that the degree to which banks can exert an influence on the price of outputs will depend on the given input prices, the given quantities of outputs and the technological constraints (Koetter, 2006). The alternative profit model has been widely used in the banking literature (Maudos et al, 2002;Bos and Kool, 2006;Koetter, 2006;Pasiouras et al, 2009;Duygun et al, 2014) Since this paper focuses on the impact of country-level environmental variables such as the cross-country variations in creditor rights and information sharing on bank profit (in)efficiency, we opt for the Battese and Coelli (1995) SFA model in order to estimate bank profit (in)efficiency 8 . This estimation of the frontier accommodates panel data and allows to 6 Efficiency estimations have some distinct advantages over accounting-based measures of performance such as financial ratios (Berger and Humphrey, 1997;Bauer et al, 1998).…”
Section: Measuring Profit (In)efficiencymentioning
confidence: 99%
“…For instance, a couple of studies have found that there exists a positive association between the value of the Tobin's q among commercial banks and their trademarking activity (Gonzalez-Pedraz and Mayordomo, 2011;Greenhalgh and Rogers, 2006). In a similar vein, Duygun et al (2014) have found that trademarking banks tend to be more profit-efficient than their non trademarking counterparts. However, we argue that trademarking may potentially affect other dimensions of a bank's performance like Total Factor Productivity growth (TFP growth, henceforth) and its components.…”
Section: Introductionmentioning
confidence: 95%